Pandangan Islam Terhadap Penentuan Akhlak Manusia Menurut Nash - Indah Kencanawati (An Nisa'a, 2012)
Polygamy is one problem in marriages among the most controversial debates at once. Polygamy is rejected with a variety of arguments normative, psychological, and even always associated with injustice gander. Islam has given the conditions on the demand of a Muslim who practice polygamy is justice to himself that he would do justice to his wives in terms of food, clothing, and living (physical and spiritual). But if he is less sure of himself to be able to do justice to his wives, he was not allowed to practice polygamy.